Diastolic hypertension is associated with proteinuria in pediatric patients. Issue 3 (9th August 2021) - Myette, Robert L.; Burger, Dylan; Geier, Pavel; Feber, Janusz
Abstract: Background and Aims: Blood pressure lability has been observed in certain cohorts of pediatric patients with variable degrees of proteinuria; however, the impact of proteinuria on blood pressure is not fully elucidated. The objective of our study was to analyze blood pressure and heart rate in pediatric patients with proteinuria. Methods: We performed a retrospective chart review of patients (age 1‐18) diagnosed with idiopathic nephrotic syndrome, with varying degrees of proteinuria. Blood pressure and heart rate data were analyzed in relation to anthropometric and biochemical parameters. A total of 72 urine sample analyses, along with associated blood pressure measurements, were obtained from the charts of 33 children (males = 25). Results: Diastolic blood pressure Z ‐scores were significantly higher in proteinuric patients (urine protein/creatinine >0.02 g/mmol) compared to non‐proteinuric patients ( P = .006; Cohen‐ d 0.97 [0.41; 1.53]). Systolic blood pressure was also significantly higher in proteinuric patients ( P = .04), but with a less significant effect size (Cohen‐ d 0.54 [−0.002; 1.08]). Proteinuria (>0.02 g/mmol) was the most significant predictor of diastolic ( β = .79, P = .04), but not systolic blood pressure elevation on multivariate analysis. Conclusions: We observed a disproportionate increase in diastolic blood pressure vs systolic blood pressure in patients with proteinuria.